Tantangan dan Solusi dalam Pengajaran Siswa Tunarungu: Persepsi Guru di SLB PGRI Kamal, Bangkalan - Raslima Simorangkir; Nova Estu Harsiwi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to understand teachers' perceptions of the challenges and solutions in teaching hearing-impaired students at SLB PGRI Kamal. The research method used is qualitative, employing data collection techniques through in-depth interviews and observations. The results show that the teachers at this school share similar perceptions regarding the challenges and solutions in teaching hearing-impaired students. The main challenges identified are the students' limited communication skills, restricted availability of media and teaching materials, and the teachers' insufficient knowledge and skills in teaching hearing-impaired students. The solutions suggested by the teachers include enhancing students' communication skills through speech and hearing therapy, providing media and teaching materials that meet the needs of hearing-impaired students, and improving teachers' knowledge and skills through training and seminars.